Removal of colour from landfill by solar photocatalytic - Salwa, Mohd Zaini Makhtar; Naimah, Ibrahim; Mohammad Tamizi, Selimin (Universiti Malaysia Sabah (UMS), 2011)
23rd Symposium of Malaysian Chemical Engineers 2009 (SOMChE 2009) in conjunction with the 3rd International Conference on Chemical and Bioprocess Engineering 2009 (ICCBPE 2009), organized by Universiti Malaysia Sabah (UMS) from 12th - 14th 2009 at Sutera Harbour Golf Resort, Kota Kinabalu, Sabah.